2011
DOI: 10.5154/r.rchscfa.2010.09.071
|View full text |Cite
|
Sign up to set email alerts
|

La Variación De Las Temperaturas Extremas en La ‘Comarca Lagunera’ Y Cercanías

Abstract: Las series de temperaturas máxima y mínima diarias, con registros de al menos 30 años, de 23 estaciones meteorológicas de la Comarca Lagunera y lugares cercanos, fueron analizadas con las técnicas de regresión lineal simple y densidad de espectro potencial para obtener las tendencias y frecuencias significativas. Las series de 15 de las 23 estaciones presentaron tendencias significati¬vas (P≤0.05) para ambas temperaturas. El promedio de las tendencias de temperatura máxima fue de -0.22 °C por decenio; pues 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
1
4
0
1
Order By: Relevance
“…Moreover, a generalized warming could be expected in the future for high elevation and southern sites in terms of maximum temperature (if the trends found here continue). Conversely, in western northern sites with high or low elevations, cooling trends might be prevailing (Table 3), as also reported by Inzunza-López et al (2011).…”
Section: Six Decades Of Climate Samplingsupporting
confidence: 73%
See 2 more Smart Citations
“…Moreover, a generalized warming could be expected in the future for high elevation and southern sites in terms of maximum temperature (if the trends found here continue). Conversely, in western northern sites with high or low elevations, cooling trends might be prevailing (Table 3), as also reported by Inzunza-López et al (2011).…”
Section: Six Decades Of Climate Samplingsupporting
confidence: 73%
“…During the period of 1950-2000, Brito-Castillo et al (2009 and Inzunza-López et al (2011) have reported anomalies regarding the generalized warming trend for Mexico (Pavia et al 2009) during the period of 1950-2000. These findings (Brito-Castillo et al 2009, Inzunza-López et al 2011 pointed out that in some sites at Northern Zacatecas and Western Durango, the actual decadal trends were rather of cooling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Localización del área de estudio. semiárido-templado con temperaturas que oscilan entre 24,66 °C y 9,37 °C y una precipitación media anual de 576 mm (Inzunza-López et al, 2011).…”
Section: áRea De Estudiounclassified
“…Several maize species found in the La Laguna region are affected by genotype and environment. In the last 30 years, climate change has caused a persistent statistical deviation with extreme temperature variations and limited water resources (Inzunza-López et al, 2011;CONAGUA, 2022). The interaction of two maize genotypes and promoters will favor germination (Ortiz-Timoteo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%